Selonsertib in adults with pulmonary arterial hypertension (ARROW): a randomised, double-blind, placebo-controlled, phase 2 trial. Issue 1 (January 2022) - Rosenkranz, Stephan; Feldman, Jeremy; McLaughlin, Vallerie V; Rischard, Franz; Lange, Tobias J; White, R James; Peacock, Andrew J; Gerhardt, Felix; Ebrahimi, Ramin; Brooks, Gabriel; Satler, Carol; Frantz, Robert P; et al.
Summary: Background: Data obtained in human lung tissue and preclinical models suggest that oxidative stress and increased apoptosis signal-regulating kinase 1 (ASK1) activity might have a prominent role in the pathobiology of pulmonary arterial hypertension (PAH). The purpose of this study was to determine the efficacy, safety, and tolerability of the ASK1 inhibitor selonsertib compared with placebo in patients with PAH. Methods: We did a randomised, double-blind, placebo-controlled, phase 2 trial at 46 centres located in Canada, France, Germany, Italy, the Netherlands, Spain, the UK, and the USA. Participants were aged 18–75 years and had an established diagnosis of idiopathic or hereditary PAH, or PAH associated with connective tissue disease, drugs or toxins, human immunodeficiency virus, or repaired congenital heart defects. Patients were stratified by PAH aetiology and background therapy, and randomly assigned (1:1:1:1) using an interactive voice-response or web-response system to placebo or selonsertib 2 mg, 6 mg, or 18 mg administered orally once daily. Both placebo and selonsertib were in tablet form. The primary efficacy endpoint was change in pulmonary vascular resistance, measured by right heart catheterisation, from baseline to week 24 in the full analysis set. Pair-wise comparisons between each of the selonsertib groups and the placebo group were made with a stratified Wilcoxon (van Elteren) rank sum test for participants without major protocol deviations who received at least one dose of study drug. This trial is registered with ClinicalTrials.gov, NCT02234141 . Findings: Between Dec 3, 2014, and Nov 13, 2015, 151 patients were enrolled and randomly assigned. Of 150 participants who received selonsertib or placebo, 134 (89%) completed 24 weeks of the randomly assigned treatment; all were on background PAH therapy (138 [92%] on combination therapy). 90 (60%) patients were in functional class II and 60 (40%) in functional class III. Mean baseline pulmonary vascular resistance was 772 (SD 334) dyn·s/cm 5 . Change in pulmonary vascular resistance was 6·0 dyn·s/cm 5 (SD 28·0; n=31) for placebo, and 35·0 (35·4) dyn·s/cm 5 (n=35; p=0·21 vs placebo) for 2 mg selonsertib, −28·0 (30·2) dyn·s/cm 5 (n=34; p=0·27 vs placebo) for 6 mg selonsertib, and −21·0 (37·9) dyn·s/cm 5 (n=36; p=0·60 vs placebo) for 18 mg selonsertib. The most frequent adverse events were headache (17 [15%]), abnormal dreams (eight [7%]), nausea (seven [6%]), and diarrhoea (seven [6%]) in the selonsertib groups, and headache (six [16%]), nausea (five [14%]), and diarrhoea (two [5%]) in the placebo group. Serious adverse events occurred in 23 (20%) of 113 selonsertib-treated patients and seven (19%) of 37 patients who received placebo. Interpretation: Selonsertib once daily for 24 weeks did not lead to a significant reduction in pulmonary vascular resistance or to clinical improvement in patients with PAH, but appeared to be safe and well tolerated. Although these data do not support the clinical use of selonsertib in PAH, further study of the potential of targeting the ASK1–p38 pathway in PAH is warranted. Funding: Gilead Sciences.